Sistem Informasi Pelayanan Surat Menyurat Desa Cibolang Kaler Berbasis Website - Dini Agnia Hardianty; Indra Yustiana (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2021)
Currently, every government agency is competing to improve the quality of its services, one of which is at the village level. Global demands require the world of government to always adapt technological developments to efforts to improve quality, especially adjusting the use of technology and communication for the world of government. Villages have a very important role in public services for the community. Management of village administration and information to enter the form system so that it is easier for the community to get information in the village. Cibolang Kaler Village is a village that has not implemented an online-based service information system. So that the making of correspondence needed by the community directly comes to the Cibolang Kaler village office. In addition, residents often complain that village services take a long time because they have to wait for queues for letters to produce letters manually. Therefore, it is necessary to have a village correspondence service information system to make it easier for residents and village officials to manage correspondence in the village of Cibolang Kaler.